2010
DOI: 10.1083/jcb.201003004
|View full text |Cite
|
Sign up to set email alerts
|

Akt/PKB suppresses DNA damage processing and checkpoint activation in late G2

Abstract: Activated Akt suppresses checkpoint activation by cells in late G2: although they are able to detect DNA damage, the repair pathway is put on hold until mitosis is complete.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
61
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 34 publications
7
61
0
Order By: Relevance
“…Recent studies have shown that activation of the ATRChk1 pathway in response to DSBs increases as cell progress through the cell cycle (Jazayeri et al, 2006;Walker et al, 2009;Xu et al, 2010). By analyzing ATRmediated Chk1 S345 phosphorylation in individual DT40 cells at defined points in the cell cycle, we find that the situation is more complex than simple restriction of DNA damage-induced ATR-Chk1 activation to the later S and G2 phases when Cdk activity is high (Jazayeri et al, 2006).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Recent studies have shown that activation of the ATRChk1 pathway in response to DSBs increases as cell progress through the cell cycle (Jazayeri et al, 2006;Walker et al, 2009;Xu et al, 2010). By analyzing ATRmediated Chk1 S345 phosphorylation in individual DT40 cells at defined points in the cell cycle, we find that the situation is more complex than simple restriction of DNA damage-induced ATR-Chk1 activation to the later S and G2 phases when Cdk activity is high (Jazayeri et al, 2006).…”
Section: Discussionmentioning
confidence: 85%
“…Chk1 activation in response to DNA damage is minimal in G1, maximal in S phase, and declines again and G2 Previously, we found that irradiation-induced Chk1 activation varies according to cell cycle position using elutriation (Walker et al, 2009;Xu et al, 2010), however, this approach did not allow comparison of levels of activation specifically in G1, S and G2/M phase. To refine this analysis, we examined the relationship between cell cycle position and Chk1 activation in individual cells.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…However, the in vitro analysis reveals that Akt/PKB phosphorylates Chk1 at several sites, among which Ser280 is only a minor phosphorylation site . In addition, Chk1-Ser280 mutants behaved like Chk1 wild type in the G2/M checkpoint (Tonic et al, 2010;Xu et al, 2010). Although Akt/PKB negatively regulates the G2/M checkpoint (Henry et al, 2001;Nimbalkar and Quelle, 2008;Shtivelman et al, 2002;Xu et al, 2010), there is a debate as to whether G2/M checkpoint is negatively regulated by Chk1-Ser280 phosphorylation.…”
Section: Chk1 Phosphorylation At Ser280mentioning
confidence: 96%
“…For instance, AKT1 destabilizes p53 via the phosphorylation of Mdm2 [54]; AKT1 controls the basal expression of XRCC1 [55]; the activation of AKT1 leads to the sequestration of CHK1 to the cytoplasm [47][48][49], and AKT1 phosphorylates and prevents the activation of CHK1 by ATR/ATM [56]; finally, AKT1 reduces the abundance of γ-gH2AX foci [57,58] in asynchronous cells, and inhibits the activation of CHK1 and the repair of DSBs at the end of G2 [59].…”
Section: Introductionmentioning
confidence: 99%